RELEVANSI NILAI INTELLECTUAL CAPITAL - Wirawan, Grace; Rachmawati, Dyna; Oki, Ariston (Jurnal Akuntansi Kontemporer, 2014)
Competition and technological developments are increasing among companies, making the company needs to focus investment knowledge assets, such as intellectual capital. Intellectual capital is not reported on the balance sheet (off-balance sheet), it will reduce information relevance to investors. This research aim to test the value relevance of intellectual capital as an off-balance sheet assets. Measurement of the value relevance of intellectual capital is done by testing the relationship between intellectual capital to firm value. Intellectual capital measurement is done by two approaches, method of accounting approaches (VAICTM) and non-accounting ap-proach (content analysis). This study also aim to prove which one of those approach have most powerful value relevance of intellectual capital. Object of this research is public companies listed on Indonesia Stock Exchange in year 2012. Total sample of this research is 138 companies selected by purposive sampling technique. Hypothesis testing using multiple linear regression. The results show that the accounting approach and non-accounting approach affects the value of the company. Non- accounting approach that is more focused on information disclosed through the annual report, giving a stronger relevance than accounting approach. This suggests that the financial information is not entirely the focus for investors in assessing the company. Other information disclosed in the annual report is also one aspect to be considered by investors.